Freedom and belief - Strawson, Galen (Oxford : Oxford University Press, 2010)
Galen Strawson examines the 'cognitive phenomenology' of freedom - the nature, causes, and consequences of our deep commitment to belief in freedom.
Previous ed.: 1986.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Free will and determinism